Genomic evidence for adaptive differentiation among Microhyla fissipes populations: Implications for conservation - Jin, Long; Liao, Wen Bo; Merilä, Juha (Diversity & distributions, 2022)
Aim Amphibians require both terrestrial and aquatic environments to complete their life cycles. Thus, they are subject to complex selection pressures stemming from different environments, and these selection pressures are likely to vary geographically with variation in temperature and precipitation. Studies of genetic differentiation along geographical clines allow identification of footprints of these selection pressures. Location China. Methods To identify possible signatures of local adaptation to particular environmental conditions, we conducted a genome‐scan with 20,572 single‐nucleotide polymorphisms (SNPs) obtained with restriction site‐associated DNA sequencing of pooled samples from 10 Microhyla fissipes populations spanning a 1,398 km long latitudinal gradient in China. Results The results revealed significant genetic differentiation among populations (FST =0.090). Numerous outlier SNPs associated with variation in both annual average temperature (n = 69) and precipitation (n = 248) were detected. Main conclusions The degree and pattern of population differentiation in the SNPs supported the hypothesis that these SNPs have been subject to directional natural selection associated with temperature and precipitation and, hence, are reflective of geographically varying local adaptation. Hence, conservation and management plans for Microhyla fissipes should take into account this heterogeneity in genetic constitution in its populations.